Addressing the Challenge of Cultivars Identification and Authentication in Mediterranean Olive Collections: A Case Study in Morocco - Ahmed, El Bakkali; Abderrahman, Mekkaoui; El Houssaini Salma, El Iraqui; Adil, Essarioui; Bouchaib, Khadari (European Scientific Journal, ESJ, 2020)
Conservation and use of well-characterized olive (Olea europaea L.) genetic resources are the key to future olive improvement and sustainable production. Yet, authentication of plant materials in ex-situ olive collections throughout the world has received little attention. Here we characterized 95 accessions, from a collection maintained in the experimental station of INRAMeknes, Morocco, by comparing their SSR (14 markers) and morphological (11 endocarp traits) profiles to an international reference dataset with 672 distinct genotypes corresponding to 535 well-described olive cultivars from the two Worldwide Olive Germplasm Banks of Marrakech, Morocco, and Cordoba, Spain (WOGB-M/C). Results revealed 122 alleles in the Meknes collection versus 265 in the reference database, but the difference was not significant. Additionally, forty cultivars were identified in Meknes collection, among which 33 were present in the reference database. Principal Coordinates Analysis revealed that these varieties span the range of all of the 535 varieties in the international database, indicating important genetic diversity within the investigated plant materials. Finally, cases of mislabeling errors, synonyms, and redundant genotypes pertaining mainly to “Picholine marocaine” and “Frantoio” varieties have been encountered in Meknes collection. Overall, our work highlights the power of coupling modern genetic and morphological tools along with exploring reference databases for authenticating genetic cultivars in olive tree collections.